Risk factors for COVID-19 case fatality rate in people with type 1 and type 2 diabetes mellitus: A nationwide retrospective cohort study of 235,248 patients in the Russian Federation - Shestakova, M. V.; Vikulova, O. K.; Elfimova, A. R.; Deviatkin, A. A.; Dedov, I. I.; Mokrysheva, N. G. (Frontiers in Endocrinology, 2022)
The Aim: to study the association of demographic, clinical, laboratory factors, the use of glucose–lowering drugs and anti-COVID-19 vaccination with the COVID-19-related case fatality rate (CFR) in DM patients. Methods: This study is a nationwide observational cohort study based on the data from the National Diabetes Register (NDR) that is the database containing online clinical information about the population with DM. The outcomes (death or recovery) for COVID-19 were registered in 235,248 patients with DM (T1DM, n=11,058 and T2DM, n=224,190) from March 20, 2020 until November 25, 2021. The unadjusted odds ratio (OR) and 95% confidence interval (CI) was used to estimate the risk factors for CFR. Results: The CFR due to COVID-19 was 8.1% in T1DM and 15.3% in T2DM. Increased CFR was associated with male population (OR=1.25 [95%CI:1.09-1.44] in T1DM and 1.18 [95%CI:1.15-1.21] in T2DM), age≥65 years (OR=4.44 [95%CI:3.75-5.24] in T1DM and 3.18 [95%CI:3.09-3.26] in T2DM), DM duration≥10 years (OR=2.46 [95%CI:2.06-2.95] in T1DM and 2.11 [95%CI:2.06-2.16] in T2DM), body mass index (BMI)≥30 kg/m2 (OR=1.95 [95%CI:1.52-2.50]) in T1DM, HbA1c≥7% (OR=1.35 [95%CI:1.29-1.43]) in T2DM. The atherosclerotic cardiovascular disease (ASCVD) and chronic kidney disease (CKD) were associated with higher CFR in T1DM, but not in T2DM. The pre-COVID-19 glucose-lowering therapy in T2DM was differently associated with CFR (OR): 0.61 [95%CI:0.59-0.62] for metformin, 0.59 [95%CI:0.57-0.61] for dipeptidyl peptidase-4 inhibitors (DPP-4 inhibitors), 0,46 [95%CI:0.44-0.49] for sodium-glucose co-transporter-2 inhibitors (SGLT2 inhibitors), 0.38 [95%CI:0.29-0.51]; for glucagon-like peptide-1 receptor agonists (arGLP-1),1.34 [95%CI:1.31-1.37] for sulfonylurea (SU) and 1.47 [95%CI:1.43-1.51] for insulin. Anti-COVID-19 vaccination was associated with lower fatality risk in both DM types: OR=0.07 [95%CI: 0.03-0.20] in T1DM and OR=0.19 [95%CI: 0.17-0.22] in T2DM. Conclusions: The results of our study suggest that increased COVID-19-related fatality risk in both T1&T2DM patients associated with male population, older age, longer DM duration and absence of anti-COVID-19-vaccination. In T2DM the pre-COVID-19 glucose-lowering therapy with metformin, DPP-4 inhibitors, SGLT2 inhibitors, and arGLP-1 had a positive effect on the risk of death.